Leptin-resistance induced hyperphagia and diminished oxidative balance in offspring of dams exposed to perinatal protein restriction (African Journal of Biomedical Research, 2021)
AbstractSubstantial evidence suggests that poor intrauterine environment produced by perinatal nutritional disturbance in both humans and animals may program susceptibility offspring to chronic diseases in life. This study investigated the role of perinatal protein restriction on food intake regulation and oxidative balance in adult offspring. Twenty-four pregnant and twelve male Sprague-Dawley rats were used. They were fed either a control diet containing 20% protein or protein-restricted (PR) diet with 8% protein. The dams were given PR diet up to parturition (in-utero group, IUPR), or from birth to post-natal day 21 (lactation group, LPR) or for a period covering both groups (combined group, CPR). Control dams with control diet was run in parallel for comparison. Food intake was determined daily and body weight measured at weekly intervals. At day 128, adiponectin, leptin and neuropeptide Y (NPY) and superoxide dismutase (SOD) catalase (CAT), reduced glutathione (GSH) and malonaldehyde (MDA) were determined. Birth weight decreased significantly (p